Filling in the (gendered) gaps: How observers frame claims of sexual assault. Issue 2 (May 2022) - Mulder, Eva; Bosma, Alice Kirsten
Claims of sexual assault are especially prone to scrutiny and (re)interpretation as something else. We investigated how people judged the veracity of sexual assault claims and how they subsequently framed their interpretations of these claims using 'general knowledge' in the form of sexual scripts, rape myths, and gender stereotypes. Participants ( n = 161) read about a sexual assault allegation by a male or female claimant and were asked to describe in more detail what they thought had happened. Data were analyzed using a combination of quantitative and qualitative frame analysis. A key finding was that although participants mostly accepted the facts of the claim, this did not automatically imply they shared the claimant's interpretation of the event as (serious) sexual assault. The analysis revealed that participants drew upon distinct frames to interpret the claim, including frames – such as regretted consensual sex and miscommunication – that exonerated the accused and emphasized claimant responsibility. Frames were differentially employed in response to male and female claims of sexual assault. We discuss how our research design and findings can contribute to an increased understanding of the underlying mechanisms of victim acknowledgment.